Near-Full Current Dynamic Range THz Quantum Cascade Laser Frequency Comb - Yu Ma; Weijiang Li; Yuanyuan Li; Junqi Liu; Ning Zhuo; Ke Yang; Jinchuan Zhang; Shenqiang Zhai; Shuman Liu; Lijun Wang; Fengqi Liu (Micromachines, 2023)
The present study proposes a terahertz quantum cascade laser frequency comb (THz QCL FC) with a semi-insulated surface plasma waveguide characterized by a low threshold current density, high power and a wide current dynamic range. The gain dispersion value and the nonlinear susceptibility were optimized based on the combination of a hybrid bound-to-continuum active region with a semi-insulated surface plasmon waveguide. Without any extra dispersion compensator, stable frequency comb operation within a current dynamic range of more than 97% of the total was revealed by the intermode beat note map. Additionally, a total comb spectral emission of about 300 GHz centered around 4.6 THz was achieved for a 3 mm long and 150 µm wide device. At 10 K, a maximum output power of 22 mW was obtained with an ultra-low threshold current density of 64.4 A·cm−2.